The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5194/nhess-14-2899-2014
|View full text |Cite
|
Sign up to set email alerts
|

A coupling of hydrologic and hydraulic models appropriate for the fast floods of the Gardon River basin (France)

Abstract: Abstract. Mediterranean catchments are regularly affected by fast and flash floods. Numerous hydrologic models have been developed, and allow modelling of these floods. However, these approaches often concern average-size basins of a few hundred km 2 . At larger scales (> 1000 km 2 ), coupling of hydrologic and hydraulic models appears to be an adapted solution. This study has as its first objective the evaluation of the performances of a coupling of models for flood hydrograph modelling. Secondly, the couplin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…Consequently, such a relatively simple coupling strategy might affect model results, but the impacts of dynamic model feedback were assumed negligible when compared to the other sources of nontrivial uncertainty (e.g., the resolution and accuracy of the topographic data). Moreover, the use of dynamic coupling for the modeling of floodplain inundation dynamics at the large scale would require extremely large computational resources that hamper both the feasibility and transferability of the methodology to other study areas (Laganier et al, 2014;Lerat, 2009). Conversely, external unidirectional coupling has been successfully applied in a number of previous analyses (Bravo et al, 2012;Lian et al, 2007;Mejia & Reed, 2011), and it was hence considered a sensible approach for the purposes of this study.…”
Section: Coupled Modeling Approach and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, such a relatively simple coupling strategy might affect model results, but the impacts of dynamic model feedback were assumed negligible when compared to the other sources of nontrivial uncertainty (e.g., the resolution and accuracy of the topographic data). Moreover, the use of dynamic coupling for the modeling of floodplain inundation dynamics at the large scale would require extremely large computational resources that hamper both the feasibility and transferability of the methodology to other study areas (Laganier et al, 2014;Lerat, 2009). Conversely, external unidirectional coupling has been successfully applied in a number of previous analyses (Bravo et al, 2012;Lian et al, 2007;Mejia & Reed, 2011), and it was hence considered a sensible approach for the purposes of this study.…”
Section: Coupled Modeling Approach and Data Analysismentioning
confidence: 99%
“…Instead of using observed rainfall records as model input, Nam et al (2014) used results from a numerical weather prediction model as input to the sequence of models for short-term flood inundation prediction. Laganier et al (2014), Nguyen et al (2016), and Mai and De Smedt (2017) showed that the coupled approach can adequately model flash floods and floodplain inundation. A coupled hydrologichydraulic modeling approach was recommended by Grimaldi et al (2013) for flood hazard modeling, by Felder et al (2017) for probable maximum flood risk estimation, and by Sindhu and Durga (2017) for flood damage mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Douinot et al: Using a multi-hypothesis framework to improve the understanding of flash flood dynamics 1.2 Flash flood events: understanding flow processes Due to the challenges involved in forecasting flash floods, there has been considerable research done on the subject over the last 10 years. Examples include the HYDRATE (Hydrometeorological data resources and technologies for effective flash flood forecasting, 2006Gaume and Borga, 2013), which enabled the setting up of a comprehensive European database of flash flood flash events as well as the development of a reference methodology for the observation of post-flood events, the EXTRAFLO (EXTreme RAinfall andFLOod estimation, 2009-2013;Lang et al, 2014) to estimate extreme precipitation and floods for French catchments, the HYMEX project (HYdrological cycle in the Mediterranean EXperiment, 2010-2020; Drobinski et al, 2014) focusing on the meteorological cycle at the Mediterranean scale and particularly on the conditions that allow extreme events to develop, the FLASH project (Flooded Locations andSimulated Hydrographs, 2012-2017;Gourley et al, 2017) assessing the ability and the improvement of a flash flood forecasting framework in USA on the basis of real-time hydrological modelling with high-resolution forcing, or the FLOOD-SCALE project (Multi-scale hydrometeorological observation and modelling for flash floods understanding and simulation, 2012-2016Braud et al, 2014), based on a multiscale experimental approach to improve the observation of the hydrological processes that lead to flash floods.…”
mentioning
confidence: 99%
“…The next step is to determine whether the discharge term is inflow or outflow fed back to the hydrodynamic model in the next time step. In this method, the current water level of the hydrologic model and hydrodynamic model have been used in velocity calculation at the mutual boundary, It does not consider present flow state (Bravo et al, 2012;Laganier et al, 2014). It is different from BCM using the lateral inflow conditions that velocity provided by hydrologic model will be added to the governing equations of hydrodynamic model directly, not considering present flow state.…”
Section: Introductionmentioning
confidence: 99%